2003
DOI: 10.1074/jbc.m302713200
|View full text |Cite
|
Sign up to set email alerts
|

Functional Implications from an Unexpected Position of the 49-kDa Subunit of NADH:Ubiquinone Oxidoreductase

Abstract: Membrane-bound complex I (NADH:ubiquinone oxidoreductase) of the respiratory chain is considered the main site of mitochondrial radical formation and plays a major role in many mitochondrial pathologies. Structural information is scarce for complex I, and its molecular mechanism is not known. Recently, the 49-kDa subunit has been identified as part of the "catalytic core" conferring ubiquinone reduction by complex I. We found that the position of the 49-kDa subunit is clearly separated from the membrane part o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
2
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 80 publications
(66 citation statements)
references
References 43 publications
4
58
2
2
Order By: Relevance
“…Therefore, it is not clear how the membrane-integral quinones can oxidize the cytoplasmic Cys180 and Cys241. In a similar case, it has been shown that reduced quinones reduce periplasmic Cys residues of the membrane-bound protein disulfide reductase DsbB (17), and the quinone site of the NADH:ubiquinone oxidoreductase seems to be distant from the membrane, too (290). Presumably, the membrane-integral quinones are able to react at sites outside the membrane, when hydrophobic parts of the protein enable emerging of the reactive head group from the membrane.…”
Section: Membrane-anchored Hks With C-terminal Cytoplasmic Sensing Domentioning
confidence: 97%
“…Therefore, it is not clear how the membrane-integral quinones can oxidize the cytoplasmic Cys180 and Cys241. In a similar case, it has been shown that reduced quinones reduce periplasmic Cys residues of the membrane-bound protein disulfide reductase DsbB (17), and the quinone site of the NADH:ubiquinone oxidoreductase seems to be distant from the membrane, too (290). Presumably, the membrane-integral quinones are able to react at sites outside the membrane, when hydrophobic parts of the protein enable emerging of the reactive head group from the membrane.…”
Section: Membrane-anchored Hks With C-terminal Cytoplasmic Sensing Domentioning
confidence: 97%
“…Purification of Complex I-Unsealed mitochondrial membranes were prepared from parental and mutant haploid strains (nukm::LEU2, ura3, leu2, lys11, pUB4-nukm mut /Hyg) as described previously (17,19). Complex I was purified by extraction of mitochondrial membranes with dodecyl maltoside followed by Ni 2ϩ -agarose and size exclusion chromatography (17).…”
Section: Methodsmentioning
confidence: 99%
“…The location shown for NuoB takes into account the direct interaction demonstrated between subunits NuoB and NuoA (47). The location of NuoCD is according to recent antibody labeling studies (48). The fact that NuoCD was readily dissociated from the otherwise intact complex under some conditions (Figs.…”
Section: Subunits Nuol and Nuom Are Removed From Complex I In Diheptamentioning
confidence: 99%